Effect of Vestibular Schwannoma Size and Nerve of Origin on Posterior External Auditory Canal Sensation: A Prospective Observational Study. Issue 9 (October 2020) - Mehta, Gautam U.; Lekovic, Gregory P.; Maxwell, Anne K.; Brackmann, Derald E.; Slattery, William H.
Abstract : Objective: Posterior external auditory canal (EAC) hypesthesia (Hitselberger's sign) has been previously described to occur in all vestibular schwannomas (1966) but has not been studied since. We hypothesized that sensory loss may be related to tumor size and sought to determine if this clinical sign could predict preoperative characteristics of vestibular schwannomas, intraoperative findings, and/or surgical outcomes. Study Design: Prospective observational study. Setting: Tertiary referral center. Patients: Twenty-five consecutive patients who underwent surgery for vestibular schwannoma. Intervention: Patients were tested for the presence of EAC hypesthesia or anesthesia. Main Outcome Measures: Preoperative, intraoperative, and postoperative findings were recorded, including facial nerve function, hearing function, tumor size, tumor nerve of origin, and extent of resection. Results: Twelve patients (48%) demonstrated either posterior EAC hypesthesia (11 patients) or anesthesia (1 patient). Sensory loss was a significant predictor of size (tumor maximal diameter) ( p  = 0.004). Median tumor diameter was 1.7 cm in the cohort with intact sensation versus 2.9 cm in the cohort with sensory loss. Patients with sensory loss were also significantly more likely to be associated with a superior vestibular nerve origin tumor ( p  = 0.01). Preoperative sensory loss did not significantly predict postoperative facial outcome ( p  = 0.10). Conclusion: Neurological exam findings may be overlooked in the workup of brain tumors. Posterior EAC hypesthesia is a predictor of tumor size and superior vestibular nerve origin. These findings may have implications for patient selection, particularly with the middle cranial fossa approach. Furthermore, given this relationship with tumor size, this clinical biomarker should be studied as a potential predictor of tumor growth.